Project Based Learning in Science with Graphing Calculator Coupled Portable Sensors - Wong, Ling Shing; Voon, Betty Wan Niu (2016)
Project based learning allows students to participate in the learning process, by allowing them to construct questions, draw hypotheses, find explanations, and discuss their idea collaboratively, which all together polish the students' thinking competency. Through simple graphing calculator coupled portable sensors, project based learning can be carried out in teaching biology related topics. In this paper, an example of project based learning in biology is reported. The students were given a few portable sensors, including light, temperature, pressure, and pH sensors which could be coupled with graphing calculator to collect data on a life culture of living algae. The possible designs from of the experiment, and the benefit of conducting the project for students are highlighted.